Improved detection of early gastric cancer with linked color imaging using an ultrathin endoscope: a video-based analysis - Khurelbaatar, Tsevelnorov; Miura, Yoshimasa; Osawa, Hiroyuki; Ino, Yuji; Takezawa, Takahito; Iwashita, Chihiro; Nomoto, Yoshie; Tsunoda, Masato; Ueno, Takashi; Takahashi, Haruo; Nagayama, Manabu; Fukuda, Hisashi; Lefor, Alan Kawarai; Yamamoto, Hironori (Endoscopy International Open, 2022)
Background and study aims Ultrathin endoscopy causes a minimal gag reflex and has minimal effects on cardiopulmonary function. Linked color imaging (LCI) is useful for detection of malignancies in the digestive tract. The aim of this study was to clarify whether LCI with ultrathin endoscopy facilitates detection of early gastric cancer (EGC) despite its lower resolution compared with high-resolution white light imaging (WLI) with standard endoscopy.Patients and methods This was a retrospective analysis with prospectively collected video, including consecutive 166 cases of EGC or gastric atrophy alone. Ninety seconds of screening video was collected using standard and ultrathin endoscopes with both WLI and LCI for each case. Three expert endoscopists assessed each video and the sensitivity of detecting EGC calculated. Color difference calculations were performed.Results Sensitivities using ultrathin WLI, ultrathin LCI, standard WLI, and standard LCI for the identification of cancer were 66.0 %, 80.3 %, 69.9 %, and 84.0 %, respectively. The color difference between malignant lesions and surrounding mucosa with ultrathin LCI and standard LCI were significantly higher than using ultrathin WLI or standard WLI, supported subjectively by the visibility score. Ultrathin LCI color difference and visibility score were significantly higher than standard WLI.Conclusions LCI with a low-resolution ultrathin endoscope is superior to WLI with a high-resolution standard endoscope for gastric cancer screening. This suggests that the high color contrast between EGC and the surrounding mucosa is more important than high-resolution images.